Tingkat Kepuasan Pengguna Terhadap Kinerja Alat Kompressi Sampah Botol Plastik “Bottlepress” Berbasis IoT - Yulanda Rizqi Ramadhini; Hikmah Rahmah; Nur Aziezah; Walidatush Sholihah; Inna Novianty (Jurnal Kendali Teknik dan Sains, 2024)
The purpose of this research is to ascertain how satisfied users are with the functionality of the IoT-based “BottlePress” plastic bottle waste compression tool. This research uses a survey method with quantitative research with a sampling technique, namely distributing online questionnaires via Google Form. A simple regression test was used to analyze data obtained from filling out the questionnaire. According to the research findings, most users are satisfied with the performance of the IoT-based “BottlePress” plastic bottle waste compression tool.